"Our" brand's failure leads to "their" product derogation. Issue 4 (18th April 2017) - Chae, Boyoun (Grace); Dahl, Darren W.; Zhu, Rui (Juliet)
Abstract: This research examines when and how consumers' product attitudes and their subsequent word‐of‐mouth behaviors are impacted by negative information about a brand that is associated with their social group. We find that negative information about an in‐group brand threatens the in‐group members' social identity, which in turn results in derogation of the threatening out‐group's product. Importantly, we identify that the communication source of the negative information determines whether a threat to social identity will be realized. The out‐group product derogation effect is observed only when the communication of the negative information comes from an out‐group (vs. in‐group) source. Finally, we provide evidence for our proposed mechanism by showing that a group affirmation exercise mitigates the out‐group product derogation effect we have identified.